2000
DOI: 10.1021/ja001891d
|View full text |Cite
|
Sign up to set email alerts
|

H-Bonding in Alcohols Is Reflected in the Cα−H Bond Strength:  Variation of C−D Vibrational Frequency and Fractionation Factor

Abstract: The variation of the C-D vibrational stretching frequency in primary and secondary alcohols containing the D-C-O-H functionality has been examined for cases in which the alcohol functions as a proton donor in an H-bond. The C-D stretching frequency is a function of the H-bond enthalpy of formation determined by Hartree-Fock calculations, decreasing by approximately 5 cm -1 per kcal/mol. This decrease in frequency is attributed to the increase in the overlap of the O-H bonding electrons with the C-D antibonding… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
58
0

Year Published

2006
2006
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 57 publications
(62 citation statements)
references
References 49 publications
3
58
0
Order By: Relevance
“…kX1000 s À1 , so that the conformational/protonation state isotopic equilibrium is maintained during the time course of the enzymatic reaction. These equilibria can be associated with 2 H equilibrium isotope effects as large as 1.15-1.20 (Williams, 1983;Anet and Kopelevich, 1986;Gawlita et al, 2000;Lewis and Schramm, 2001 are well known especially with regards to sugar metabolism (Schray and Benkovic, 1978). Lewis and Schramm have provided a comprehensive review of such influences on the observed V/K isotope effect (Lewis and Schramm, 2006).…”
Section: Substrate Equilibrium Isotope Effectsmentioning
confidence: 99%
See 2 more Smart Citations
“…kX1000 s À1 , so that the conformational/protonation state isotopic equilibrium is maintained during the time course of the enzymatic reaction. These equilibria can be associated with 2 H equilibrium isotope effects as large as 1.15-1.20 (Williams, 1983;Anet and Kopelevich, 1986;Gawlita et al, 2000;Lewis and Schramm, 2001 are well known especially with regards to sugar metabolism (Schray and Benkovic, 1978). Lewis and Schramm have provided a comprehensive review of such influences on the observed V/K isotope effect (Lewis and Schramm, 2006).…”
Section: Substrate Equilibrium Isotope Effectsmentioning
confidence: 99%
“…The initial binding step requires the desolvation of the alcohol. Both theoretical and experimental investigations indicate that the loss of water as an H-bond donor to the oxygen results in a significant decrease in the stretching frequency of the adjacent C-H bond (Gawlita et al, 2000;Maiti et al, 2003). These observations predict a depletion of D in the desolvated initial enzyme-substrate complex (a normal binding effect).…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation
“…The isotope effects in this figure are based on gas phase calculations and can therefore be regarded as slightly more inverse than might be expected for a solvated hydroxymethylene reactant undergoing nucleophilic attack in an enzyme active site. This is because the solvated alcohol will function as a hydrogen-bond acceptor with water, which will reduce the electron density at the hydroxyl thereby stiffening the C-H bonds of the methyl group [23,54]. Desolvation will therefore lead to a loosening of the bonds and a normal isotope effect.…”
Section: Nucleophilic Attack By Methanolmentioning
confidence: 99%
“…The stiffness of these bonds is sensitive to both the orientation and H-bonding status of the adjacent hydroxyl. In aqueous solution complete ionization leads to secondary deuterium isotope effects on the order of 6% per C-H bond [23]. Likewise, desolvation and H-bonding in the active site of thymidine phosphorylase has been shown to produce a tritium binding equilibrium isotope effect on the order of 6% per C-H bond [24,25].…”
Section: Introductionmentioning
confidence: 99%